(untitled) (Research, Society and Development, 2020)
This study aims to analyze the effects of credit granting of PRONAF, in the economy of Canguçu/RS, a municipality with the largest number of smallholdings of Brazil. We used time series, with data from the Special Secretariat for Family Agriculture and Agrarian Development (SEAD) and the Brazilian Institute of Geography and Statistics (IBGE). The methodology comprises the use of unit root test, Johansen cointegration test and Granger causality test. We interviewed leaders who work in the execution of the program in Canguçu in order to learn about the impact of PRONAF on the local economy, income and quality of life for family farmers. The results suggest that an increase in PRONAF resources tends to grow the municipality’s GDP. The interviews show that PRONAF positively impacts the economic development of Canguçu, fulfills its role in improving the income conditions and quality of life of family farmers.